Survival rates of familial and sporadic prostate cancer patients - Plonis, J.; Nakazawa-Miklasevica, M.; Malevskis, A.; Vaganovs, P.; Pildava, S.; Vjaters, E.; Gardovskis, J.; Miklasevics, E. (Experimental Oncology, 2015)
Aim: To compare cancer-specific survival rates for familial and sporadic prostate cancer patients. Materials and Methods: Gleason score and age at diagnosis of familial group and sporadic group were compared by χ² and t-test. Cancer-specific survival rates were analyzed by the Kaplan — Meier method and compared by log-rank test. Statistically significant level was set at p < 0.05. Results: Among 1175 prostate cancer patients, familial group consisted of 215 (18.3%) patients, the sporadic group consisted of 960 (81.7%) patients. The familial group patient’s mean age at diagnosis (58.9 years old, 95% confidence interval (CI) 57.8–60.1) was significantly younger than that of sporadic group patients (67.2 years old, 95% CI 66.7–67.6) (p < 0.0001). Comparing Gleason score between familial group and sporadic group revealed no statistically significant difference. The analysis showed that 92% (95% CI 0.88–0.97) of familial group patients had a 10-year cancer-specific survival rates, which was a significantly better outcome than that of sporadic group with 69% (95% CI 0.60–0.78) 10-year cancer-specific survival rates (p = 0.0237). Conclusion: The study data demonstrate statistically significant difference between familial group and sporadic group concerning age and cancer-specific survival rates, but not Gleason score. Key Words: prostate cancer, hereditary, familial, survival rates.